(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
(Matthew 24:14; 28:19, 20) Today, the extent to which this system is protected plays an important role in the development of information systems and the development of its project. The protection of information systems is significant not only by how strongly the authentication and identification system is installed, but also by the extent to which users’ rights are limited.